Key Elements of a State Regulatory Framework for Managed Aquifer Recharge. Issue 5 (25th August 2022) - Doremus, Llyn; Job, Charles
Abstract: The regulation and permitting of managed aquifer recharge (MAR) has largely been integrated within existing State groundwater regulations. MAR implementation encompasses associated processes that include: (1) source water acquisition and conveyance to the recharge site; (2) source water treatment to ensure compatibility with native groundwater, (3) aquifer capacity to receive recharged water; (4) migration and recovery of recharged water; (5) geochemical reactions of injected water with aquifer matrix and native groundwater; and (6) monitoring and mitigation measures as required. Characterization, design, and operation of the various components involved in successfully recharging groundwater over extended duration is evolving and depends in part on effective coordination and communication between MAR project proponents and regulators. Sustained groundwater availability will depend upon investment in development of effective managed aquifer recharge regulations that are practical, not overly burdensome and support water supply resiliency. MAR has a history of at least 100 years in the United States typically, but not exclusively, in the southwest due to more arid conditions. Regulation and permitting of MAR projects developed over that time vary substantially between states. Implemented properly, MAR project permitting and compliance provide critical oversight to protect water quality and water rights. The MAR regulatory components presented here are intended to inform future development of more consistent and effective regulation across the United States to facilitate investment in their installation and operation.